PENENTUAN AWAL BULAN HIJRIAH (Studi Hadis tentang Hilal sebagai Tanda Awal Bulan Hijriah) - Nadhifah, Zahrotun (UIN ALAUDDIN MAKASSAR, 2020)
Hadith which is includes “fasting because you see the new moon and breaking the fast because seeing the new moon” becomes the basis of reference that the new moon is the initial sign of entry not only in the month of Ramadan and Shawwal but also the 12th month of Hijri. At the time of the Prophet the determination of the beginning of the Hijri month was only by the rukyat method, namely seeing the new moon with the naked eye, then developing other methods such as reckoning and new criteria that followed. Rukyat is a method to find out the new moon by looking at the 29th of the month, if it is not visible, it will be completed in 30 days. Reckoning is a method to determine the appearance of the new moon with a calculation, if it is above the horizon then enter the beginning of the Hijri month. Regarding the debate and the difference between the methods used in seeing the new moon is not a problem, because it is part of the ‘urf (tradition), not a worship that has been determined by Allah and His Messenger. The best method of establishing the lunar month is the right and right method, uniting the reckoning with rukyat, without the need for a dichotomy between the two.Keywords: Hadith, hilal, beginning of Hijri.